Internal customer satisfaction via precaution of occupational health and safety being accurately accomplished while manufacturing end product made of glass fiber reinforced polymer by means of integrated management - (:unkn) unknown (International Foundation for Production Research (IFPR), 2015)
In nowadays' technology, with the emergence of the energy savings in material selection, fiber reinforced plastic, used instead of conventional metal, being both lighter and having higher rates of the density of strength, has been preferred. The glass fibers are woven to form cloth which can be bonded together by a resin, usually a thermosetting polymer matrix, to form a composite material called glass fiber reinforced polymer (GFRP). Besides fiberglass, other materials such as graphite or aramid are also used as reinforcement. These materials have to be used in wide application fields, especially such as aviation industry, marine application, automobile, wind power plant, storage tank, roof and surfboard etc. While manufacturing these kinds of products made of GFRP are used in many chemicals that contain hazardous substances, they may cause injury or ill health to workers. In this study, we investigated GFRP with regard to occupational health and safety in the course of manufacturing of end product. And precaution of occupational health and safety was evaluated for internal customer satisfaction in the products by means of integrated management.
Keywords: Glass fiber reinforced polymer (GFRP); Integrated Management; Internal Customer Satisfaction; Manufacturing; Occupational health and safety